BUSINESS SUSTAINABILITY: HOW TO ENGAGE CUSTOMERS DURING THE PANDEMIC - Devi Rachmasari (Politeknik Ubaya, 2021)
It is a worldwide condition that corona virus spread at the end of 2019. The lockdown policy applied in most countries in the world as an effort to break the chain of spread of the virus, unfortunately, has a big impact on economics activities. The business must think hard in order to be able to sustain. Thus the writer wants to analyze a case in a language course in Surabaya to be able to survive and engage customers during the pandemic by using descriptive qualitative study with a case study. The strategy of new mindset and digital marketing is proved to be effective in making the course sustains during the pandemic of covid 19. The long distance and lockdown condition is no longer a matter since through digital marketing, the course is able to reach the public to be customers.